2004
DOI: 10.1007/s00335-004-2356-6
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in equine immune response genes and their associations with infections

Abstract: Polymorphic markers identified in the horse genes encoding the interleukin 12 p40 subunit, interferon gamma, tumor necrosis factor receptor 1, and inducible nitric oxide synthase were identified and tested, along with additional markers, for associations with two important horse infections: Rhodococcus equi and Lawsonia intracellularis. Eight immune response-related and 14 microsatellite loci covering 12 out of 31 equine autosomes were used for the association analysis. Markers located on horse Chromosomes Eca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 28 publications
0
19
1
Order By: Relevance
“…In our study, no genomic regions associated with IBH were found on ECA14. Hořin et al [46] investigated polymorphisms in various immune response related genes to identify associations with R . equi and L .…”
Section: Discussionmentioning
confidence: 99%
“…In our study, no genomic regions associated with IBH were found on ECA14. Hořin et al [46] investigated polymorphisms in various immune response related genes to identify associations with R . equi and L .…”
Section: Discussionmentioning
confidence: 99%
“…More work is needed to understand the risk factors for the development of N‐EPE, which could include environmental/husbandry differences, genetic polymorphisms, the infectious dose, L. intracellularis strain, concurrent disease, or animal's immune status. Our previous work with an experimental challenge model seems to suggest that the host immune system likely plays the largest role in this type of clinical presentation as the infectious dose and strain used in that study was consistent across 6 challenged weanlings, yet only 1 developed N‐EPE; however, based on the occurrence of 2 N‐EPE cases on the same farm in consecutive years, a significant role of bacterial strain cannot be ruled out.…”
Section: Discussionmentioning
confidence: 99%
“…Frequencies of variants (not in parenthesis) are shown for each breed/species and dashes indicate the variant is not found in a given breed/species. Breed and susceptibility to R equi pneumonia, 30 but this study used a PCR restriction fragment length polymorphism method permitting detection of only 4 of the variants in the 59UTR region, not including the -57C/T polymorphism.…”
Section: Discussionmentioning
confidence: 99%
“…polymorphism involved in natural resistance to R equi pneumonia, because the disease was detected in foals from Farm A that were fixed for the -57C allele (presumptively associated with foals exposed but not infected with R equi pneumonia based on the data from Farms B and C; Table 3). Two other equine gene regions have been associated with the presence of high numbers of R equi in TBA fluid, 30…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation